2019
DOI: 10.21014/acta_imeko.v8i4.682
|View full text |Cite
|
Sign up to set email alerts
|

Using a qualitative and quantitative validation methodology to evaluate a drone detection system

Abstract: Now that the use of drones is becoming more common, the need to regulate the access to airspace for these systems is becoming more pressing. A necessary tool in order to do this is a means of detecting drones. Numerous parties have started the development of such drone detection systems. A big problem with these systems is that the evaluation of the performance of drone detection systems is a difficult operation that requires the careful consideration of all technical and non-technical aspects of the system un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…There is no automatic system in place for law enforcement agencies to detect airspace contravention caused by UAVs. Solutions are still under development or at infant stages in development [8][9][10]. Having this solution will enable law enforcement to tackle UAV crimes.…”
Section: Introductionmentioning
confidence: 99%
“…There is no automatic system in place for law enforcement agencies to detect airspace contravention caused by UAVs. Solutions are still under development or at infant stages in development [8][9][10]. Having this solution will enable law enforcement to tackle UAV crimes.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of planning can be one of the critical triggering factors to the use of User-Centred Design, which should be focused and integrated into all phases of the system life cycle [8] [9]. Testing and operational validation during each of the stages of the design process (requirements identification, proof of concept development, prototype development, final product development) is absolutely necessary, as it is often very difficult for the designers of a product to understand intuitively [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the report by Bard College's Center for the Study of the Drone [3] found that 327 incidents between December 2013 and September 2015 (USA only) posed a "proximity danger" where an unmanned aircraft got within 500 feet (152.4 m) of a plane, helicopter, or other manned aircraft (involved multiengine jet aircraft). The above mentioned, as well as similar accidents, have caused many institutions to Many scientists and engineers involved in the development of anti-drone systems agree that a multi-sensor system could provide a higher probability of drone detection than a single sensor [6][7][8][9][10][11][12]. Experiments also suggest that one of the most efficient detectors of UAV is a frequency modulated continuous wave (FMCW) radar [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The above mentioned, as well as similar accidents, have caused many institutions to Many scientists and engineers involved in the development of anti-drone systems agree that a multi-sensor system could provide a higher probability of drone detection than a single sensor [6][7][8][9][10][11][12]. Experiments also suggest that one of the most efficient detectors of UAV is a frequency modulated continuous wave (FMCW) radar [6][7][8][9][10][11][12]. It has a big detection range, transmits low power [13], and is independent of electromagnetic signals and sounds emitted by drones (UAV operating in a fully autonomous mode and gliding can be detected, too).…”
Section: Introductionmentioning
confidence: 99%